تحليل معنى الإيجاز في الكلام في تفسير آيات القرآن في سورة الإخلاص (The Meaning of Ijaz Fil Kalam In Interpreting Surah Al-Ikhlas In Holy Qur'an) - Samosir, Anggun Salsabila; Ananta, Puji Aulia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the meaning of ijaz fil kalam (concise eloquence in speech) in interpreting the verses of the Qur’an, specifically within Surah Al-Ikhlas. The phenomenon of ijaz—a hallmark of rhetorical beauty and brevity in classical Arabic—plays a critical role in revealing profound meanings in minimal wording, especially in divine revelation. Employing a qualitative descriptive approach, this study utilizes content analysis through a library research method. The primary data source is the text of Surah Al-Ikhlas, examined through the lens of classical balaghah theory and the interpretations of authoritative exegetes such as Al-Raghib Al-Asfahani, Al-Zamakhshari, and Fakhruddin Al-Razi. Findings reveal that each verse in Surah Al-Ikhlas contains distinct forms of ijaz, including ijaz hadhf (omission), ijaz qasr (restriction), and ijaz tarkib (structure), collectively reinforcing the concept of divine oneness in a concise and impactful manner. This contributes significantly to the linguistic and theological understanding of the Qur’an, offering a basis for interpretive approaches that are more attuned to rhetorical structures. The study's implications span Islamic education, Qur’anic exegesis, and Arabic language instruction, recommending the integration of balaghah-based analysis in contemporary tafsir studies. Further research is suggested to explore ijaz in other short surahs with varied da’wah contexts.